Three-phase four-wire circuits interpretation by means of different power theories - Marafão, Fernando P. [UNESP]; Liberado, Eduardo V. [UNESP]; Paredes, Helmo K.M.; Da Silva, Luiz C.P. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
In order to contribute to the discussion of defining a generalized power theory, valid for unbalanced and non linear circuits, this paper discusses the relationship and discrepancies among four modern power theories. Three-phase four-wire circuits, under different conditions, have been analyzed, since the most conflicting and intriguing interpretations take place in case of return conductor occurrence. Simulation results of different load, power supply and line conditions will be discussed in order to elucidate the author's conclusions and to provoke the readers for additional discussions. © 2010 IEEE.
Keywords: Apparent power; Distortion power; Nonsinusoidal systems; Power factor; Power theories; Unbalanced systems; Power factors; Power theory; Electric converters; Electric power factor; Electric wiring; Wire; Technical presentations